Mentoring Education Administration Land through Activity Internship in the Field Settlement Land Office Dispute Regency Pasuruan - Relys Sandi Ariani; Fidela Dzatadini Wahyudi; Si Yusuf Al Hafiz; Milka Kumala; Nanik Agustiningrum (Universitas Kristen Cipta Wacana, 2026)
Problem administration land Still be one of reason main emergence dispute land in Indonesia. The low literacy public about procedure registration land. land data maintenance, and mechanism settlement dispute cause increasing potential conflicts that result in uncertainty law. Community service program to public This aim increase understanding public about administration land through mentoring educational activities carried out by student internship in the field Settlement Land Office Dispute Regency Pasuruan Activities implemented use approach Participatory Learning and Service (PLS) which integrates observation service assistance consultation. education law land as well as reflection learning. Target activity covering community consultation about dispute land, applicant service land, as well as student participant internship. Activity results show improvement understanding public to procedure administration land, mechanism settlement disputes, and the importance of completeness document ownership. Share students, activities give experience Study contextual about implementation service public and settlement dispute land. Collaboration between college height and Land Office proven become an effective learning model in increase literacy law land at a time support improvement quality service public